2018
DOI: 10.1080/13501763.2018.1497075
|View full text |Cite
|
Sign up to set email alerts
|

Opportunity or threat? Public attitudes towards EU freedom of movement

Abstract: This article examines the effect of individual and contextual variables on preference formation towards European Union (EU) freedom of movement. Our multilevel analyses of Eurobarometer data show that citizens with low levels of human capital and strong feelings of national identity are more likely to oppose intra-EU migration. However, we argue that in order to fully grasp variation in public preferences, we need to consider the domestic context. Utilitarian and affective theories have more explanatory power … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
66
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(72 citation statements)
references
References 38 publications
3
66
1
2
Order By: Relevance
“…The last step in the empirical analysis examined potential heterogeneous effects based on ideology. 11 Previous work has suggested that people on the right of the political spectrum are less likely compared to those on the left of the political spectrum to support financial aid to other member states or the extension of rights to EU citizens (Kuhn et al 2017;Vasilopoulou and Talving, 2018). In addition, historically the left has been quite wary of the establishment of a European army (Hofmann, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The last step in the empirical analysis examined potential heterogeneous effects based on ideology. 11 Previous work has suggested that people on the right of the political spectrum are less likely compared to those on the left of the political spectrum to support financial aid to other member states or the extension of rights to EU citizens (Kuhn et al 2017;Vasilopoulou and Talving, 2018). In addition, historically the left has been quite wary of the establishment of a European army (Hofmann, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The results resonate well with insights from existing research on public opinion towards the integration of other core state powers, such as control of labour markets, welfare, enlargement and foreign and defence policy (Bechtel et al ., ; Franchino and Segatti, ; Gerhards and Lengfeld, ; Hainmueller and Hiscox, ; Irondelle et al ., ; Kentmen, ; Maier and Rittberger, ; Schoen, ; Vasilopoulou and Talving, ). After controlling for socioeconomic background, respondents' collective identity as European correlates with above average levels of support for an open intra‐EU regime both inside and outside Schengen.…”
Section: Discussionmentioning
confidence: 99%
“…One should therefore expect that individuals' self‐declared and therefore conscious origin should be particularly relevant for those who were previously excluded from Schengen and have recently been included. If there is an impact of migration on attitude, one would expect it to be particularly pronounced among central and eastern Europeans:H2a A migration background is positively associated with support for an open intra‐EU border regime.H2b This positive association is particularly pronounced among respondents whose countries of origin have been recently granted Schengen membership.The literature makes contradictory claims about the relevance of contextual factors on the impact of identity (Lubbers and Scheepers, ; Sides and Citrin, ; Vasilopoulou and Talving, ). One line of argument stresses that identity becomes relevant for attitude formation only if objective pressures make the impact of the European integration salient to Europeans (Garry and Tilley, ).…”
Section: Identity and Support For European Border Regimesmentioning
confidence: 99%
See 2 more Smart Citations